Peran Persepsi Kontrol Perilaku dalam Memediasi Pengaruh Pengetahuan Kewirausahaan terhadap Intensi Kewirausahaan Digital - Alifah Kusumaningrum; Kusnendi Kusnendi; Dian Herdiana Utama (Ideas Publishing, 2022)
The results of this study show perceived behavioral control in mediating the effect of entrepreneurial knowledge on the intensity of digital entrepreneurship. The sample of reasearch are 136 students/I SMK Negeri in West Jakarta Class X majoring in bold and digital business. This study uses a structural equation model analysis tool (PLS-SEM analysis) with the SmartPLS 3.0 application. The results show that entrepreneurial knowledge has a direct effect on the intensity of digital entrepreneurship in State Vocational High School students in West Jakarta which has a path coefficient of 0.230 and a p-value of 0.011 <0.050. Entrepreneurial knowledge has a significant positive effect on the intensity of digital entrepreneurship which is mediated by the perception of behavioral control in students/I SMK Negeri in West Jakarta which has a path coefficient of 0,102 and a p value of 0,009 < 0,050.